High-strength, high-hardening, ultra-high-performance concrete and its preparation method

JP2024545851AActive Publication Date: 2024-12-13QINGDAO UNIV OF TECH
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
JP2024527856
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2021-12-22
Filing Date
2022-01-14
Publication Date
2024-12-13
Estimated Expiration
2042-01-14

AI Technical Summary

Benefits of technology

【0022】 本発明において、赤泥の高いアルカリ性は、超高性能コンクリート(UHPC)スラリーのアルカリ濃度を大幅に改善し、セメントの水和を促進し、誘導期間を短縮し、凝縮を加速し、早期強度を改善することができ、かつ、赤泥の粒径が低い(シリカフュームとセメントとの間にある)ため、水化生成物に核生成部位を提供し、水和を加速し、凝縮時間の短縮と早期強度の改善を実現することもでき、これに基づき、セメントベースの材料と鉱物の組成を最適化することにより、赤泥の火山灰効果と充填効果が完全に再生され、超高強度、優れた耐久性のあるセメントベース材料の調製が達成される。本発明は、いくつかのゲル材料を置き換えるために赤泥を超高性能コンクリートに添加し、赤泥の蓄積とそれがもたらす環境汚染の問題を軽減し、セメントやシリカフュームなどのゲル材料の使用量を減らし、CO2の排出量を削減し、超高性能コンクリートのコストを削減し、赤泥の安全なリサイクルと利用を促進し、かつ、本発明によって提供される早強速硬型の超高性能コンクリート構造は密集しており、赤泥のアルカリ液の浸出により良いシールド効果を与えることができる。最後に、本発明により提供される早強速硬型の超高コンクリートは、赤泥の放射性を遮蔽し、放射性リスクを大幅に減少させることができ、赤泥系の超高性能コンクリート部材の安全性と長期的な運用とメンテナンスに役立ち、赤泥の安全、効率、高い割り当てのリサイクルを実現する。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2024545851000001
    Figure 2024545851000001
  • Figure 2024545851000002
    Figure 2024545851000002
  • Figure 2024545851000003
    Figure 2024545851000003
Patent Text Reader

Abstract

The present invention provides a rapid hardening ultra-high performance concrete and its preparation method and application. The components of the provided ultra-high performance concrete include red mud, silica fume, cement, quartz sand, water reducing agent, water and steel fiber. The red mud is added to the ultra-high performance concrete, and can be used to replace some commercial accelerators or gel materials for rapid hardening without the need for firing activation or dealkalization treatment for the red mud. It can effectively reduce the deposition of solid waste red mud in landfills, reduce the amount of gel materials such as cement used in the ultra-high performance concrete, reduce the CO2 emissions and costs during the preparation process of the ultra-high performance concrete, and promote the safe recycling and reuse of red mud. The provided rapid hardening ultra-high performance concrete has fast early strength evolution, high later strength, dense system, rapid structure formation, and can effectively inhibit the alkaline liquid leaching and radioactive radiation of red mud.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] (CROSS REFERENCE TO RELATED APPLICATIONS) This application claims priority to a Chinese patent application filed with the China Patent Office on December 22, 2021, with application number CN202111580483.3 and title "High-early hardening ultra-high performance concrete and its preparation method and application", the entire contents of which are incorporated herein by reference.

[0002] The present invention relates to the technical field of concrete, and in particular to an ultra-high performance concrete with high early strength and rapid hardening, and its preparation method and application. [Background technology]

[0003] Red mud is an alkaline solid waste generated in the alumina production process, and depending on the grade of bauxite, 1 to 1.5 tons of red mud are generated to produce 1 ton of alumina. Currently, red mud is mainly disposed of by landfilling, which not only occupies a large amount of land, but also causes a series of environmental problems such as land salinization and groundwater pollution due to the alkaline leaching caused by the high alkalinity of red mud (pH value 10 to 12.5).

[0004] At present, the main means of recycling red mud include preparation of adsorbents, extraction of valuable metals and production of cement. However, red mud (especially Bayer process red mud) exhibits strong alkalinity (pH>10), so in the above recycling, the red mud needs to be dealkalized or neutralized using acidic neutralizers, which increases the cost and difficulty of recycling red mud. From the perspective of cement hydration, the high alkalinity performance of red mud accelerates the hydration of cement, and promotes the setting and hardening of concrete and the achievement of early strength. However, when the amount of red mud mixed is low (mixing amount <150 kg / m 3 ), the supply of alkali is insufficient, and the early strength effect brought about is limited; while a high amount of red mud provides a rapid hardening effect, it brings about a significant deterioration in concrete performance; and the large amount of red mud mixed in increases the radioactive risk of the product.

[0005] In summary, existing red mud recycling and reuse technologies have problems such as complicated processes (requiring a dealkalization pretreatment process) and questionable anti-alkali and radioactive performance of the products. Summary of the Invention [Problem to be solved by the invention]

[0006] The present invention aims to provide an ultra-high performance concrete with rapid hardening and early strength, and its preparation method and application. The present invention adds red mud as an early hardening agent in a large amount to ultra-high performance concrete, and under the premise of ensuring the excellent mechanical properties and durability of the product, the solidification time of concrete is greatly shortened, the evolution of early strength is promoted, and at the same time, the accumulation of red mud and the resulting environmental pollution problems are alleviated, and the leaching of alkaline liquid from red mud and the radioactive risks are greatly reduced. [Means for solving the problem]

[0007] To achieve the above objectives, the present invention provides the following technical solutions: The present invention provides an ultra-high performance concrete of the rapid hardening type, which, when calculated by mass fraction, has the following properties: It contains the following ingredients: 110-180 parts red mud, 70-80 parts silica fume, 130-290 parts cement, 400-500 parts quartz sand, 10-15 parts water reducer, 80-100 parts water and 50-75 parts steel fiber.

[0008] Preferably, the particle size of the quartz sand is 0.075 to 0.6 mm; The particle size of the red mud is 0.01 to 0.075 mm; The silica fume has an average particle size of 300 nm and an activity index of ≧100%.

[0009] Preferably, the water reducing agent is a polycarboxylic acid-based high-performance water reducing agent, the fixed content of the polycarboxylic acid-based high-performance water reducing agent is 20%, and the water reduction rate is ≧35%.

[0010] Preferably, the cement is normal Portland cement having a strength level of 52.5.

[0011] Preferably, the steel fibers have a length of 13 mm, a diameter of 0.65 mm, a tensile strength of ≧2000 MPa, and the steel fibers are long and straight copper-plated steel fibers.

[0012] Preferably, the red mud is Bayer process red mud.

[0013] Preferably, the specific gravity of the quartz sand is 2560 kg / m 3 It is.

[0014] The present invention also provides a method for preparing the high-speed hardening ultra-high performance concrete described in the above technical solution, comprising: performing a first mixing process on the silica fume, cement, quartz sand and red mud to obtain a first premixture; performing a second mixing process on the first premix, water, and a water reducing agent to obtain a second premix; and performing a third mixing on the second premix and the steel fibers to obtain the high-speed hardening ultra-high performance concrete.

[0015] Preferably, the mixing time of the first mixing is 120 to 180 s, the mixing time of the second mixing is 240 to 360 s, and the mixing time of the third mixing is 60 s.

[0016] The present invention also provides the application of the rapid hardening ultra-high performance concrete according to the above technical solution or the rapid hardening ultra-high performance concrete obtained by the preparation method according to the above technical solution in building materials or decorative materials.

[0017] Preferably, the application comprises: A step of injecting a high-speed hardening ultra-high performance concrete into a mold, and then vibrating, leaving and demolding the mold to obtain a prefabricated member; maintaining the prefabricated element under steam maintenance conditions; or Or, and sequentially performing injection and laminate maintenance on the high-speed hardening ultra-high performance concrete.

[0018] Preferably, the vibration time is 60 to 180 s.

[0019] Preferably, the standing time is 3 hours.

[0020] Preferably, the steam maintenance conditions include increasing the temperature to 45°C at a rate of 5°C / min, performing preventive maintenance for 12 hours, then increasing the temperature to 100°C at a rate of 11°C / min, performing steam maintenance for 6 hours, and finally cooling to room temperature at a rate of 6.7°C / h.

[0021] The present invention provides an ultra-high performance concrete of the rapid hardening type, which contains, calculated by mass fraction, 110-180 parts of red mud, 70-80 parts of silica fume, 130-290 parts of cement, 400-500 parts of quartz sand, 10-15 parts of water reducer, 80-100 parts of water, and 50-75 parts of steel fiber. Effect of the Invention

[0022] In the present invention, the high alkalinity of red mud can greatly improve the alkali concentration of ultra-high performance concrete (UHPC) slurry, promote the hydration of cement, shorten the induction period, accelerate condensation, and improve early strength; and because the particle size of red mud is low (between silica fume and cement), it can also provide nucleation sites for hydration products, accelerate hydration, shorten the condensation time, and improve early strength; on this basis, by optimizing the composition of cement-based materials and minerals, the volcanic ash effect and filling effect of red mud are fully reproduced, and the preparation of ultra-high strength, excellent and durable cement-based materials is achieved. The present invention adds red mud to ultra-high performance concrete to replace some gel materials, alleviating the problems of red mud accumulation and the environmental pollution it brings, reducing the amount of gel materials such as cement and silica fume used, reducing CO2 emissions, reducing the cost of ultra-high performance concrete, promoting the safe recycling and utilization of red mud; and the ultra-high performance concrete structure of the early-strength and fast-hardening type provided by the present invention is dense, which can provide a better shielding effect to the leaching of alkaline liquid of red mud. Finally, the rapid hardening ultra-high performance concrete provided by the present invention can shield the radioactivity of red mud and significantly reduce the radioactive risks, which is beneficial for the safety and long-term operation and maintenance of red mud-based ultra-high performance concrete components, and realizes the safe, efficient and high-allocation recycling of red mud.

[0023] The test results of the embodiment show that the amount of alkaline leaching of the high-speed hardening ultra-high performance concrete provided by the present invention is low, meets the standard of the "Method for Determining Leachable Harmful Substances in Wall Materials", and the radioactive nuclide value is significantly reduced compared with red mud, and the internal irradiation index I Ra and external irradiation index I r The values ​​are all smaller than that of red mud and smaller than 1, meeting the internal irradiation index index and external irradiation index index required by Chinese standards.

[0024] The present invention also provides a method for preparing the rapid-hardening ultra-high performance concrete described in the above-mentioned solution, in which the present invention obtains a rapid-hardening ultra-high performance concrete by mixing and preparing each component, and avoids settling and deposition of components while ensuring sufficient dispersion of particles and hydration of gel material.

[0025] The present invention also provides the application of the high-speed hardening ultra-high performance concrete described in the above solution, and the high-speed hardening ultra-high performance concrete provided by the present invention can be applied to building materials and decorative materials. The high-speed hardening ultra-high performance concrete provided by the present invention is reddish brown in color and has a certain appearance beautification effect, and this material meets the requirements of national standards GB6566-2010 "Controlled amount of radioactive nuclides in building materials" and GB / T39804-2021 "Method for the determination of leachable harmful substances in wall materials", reduces the cost of building materials, meets the requirements of safety, economy, environmental protection, etc., and can be applied to roads, bridge panel pavements, prefabricated components, and reduces costs and shortens the construction period while ensuring the safe and stable operation and maintenance of the components. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0026] The present invention provides an ultra-high performance concrete of the rapid hardening type, which, when calculated by mass fraction, has the following properties: It contains the following ingredients: 110-180 parts red mud, 70-80 parts silica fume, 130-290 parts cement, 400-500 parts quartz sand, 10-15 parts water reducer, 80-100 parts water and 50-75 parts steel fiber.

[0027] Unless otherwise specified, there are no special requirements for the source of each component in the high-early hardening, high-performance concrete described in the present invention, and any source known to those skilled in the art may be used.

[0028] When calculated by mass fraction, the ultra-high performance concrete of the high-early hardening type provided by the present invention contains 110-180 parts of red mud, preferably 115-179 parts, more preferably 119-178 parts. In the present invention, the particle size of the red mud is preferably 0.01-0.075 mm, more preferably 0.02-0.06 mm, and even more preferably 0.03-0.05 mm. In the present invention, the red mud is preferably red mud by the Bayer process.

[0029] Based on the mass fraction of the red mud, the high-early hardening ultra-high performance concrete provided by the present invention contains 70-80 parts of silica fume, preferably 71-78 parts, more preferably 72-76 parts. In the present invention, the average particle size of the silica fume is preferably 300 nm. In the present invention, the activity index of the silica fume is preferably ≧100%. In one embodiment of the present invention, the silica fume is preferably purchased from EKG Company.

[0030] Based on the mass fraction of the red mud, the high-early hardening ultra-high performance concrete provided by the present invention contains 130-290 parts of cement, preferably 140-280 parts, more preferably 150-270 parts. In the present invention, the cement is preferably a normal Portland cement having a strength level of 52.5.

[0031] Based on the mass fraction of the red mud, the high-early hardening ultra-high performance concrete provided by the present invention contains 400 to 500 parts of quartz sand, preferably 410 to 490 parts, and more preferably 420 to 480 parts. In the present invention, the particle size of the quartz sand is preferably 0.075 to 0.6 mm, more preferably 0.1 to 0.5 mm, and even more preferably 0.2 to 0.4 mm. In the present invention, the quartz sand preferably has a continuous particle size distribution and a specific gravity of preferably 2560 kg / m 3 In an embodiment of the present invention, the quartz sand is preferably purchased from Hunan Yangmao Quartz Sand Filter Co., Ltd.

[0032] Based on the mass fraction of the red mud, the high-early hardening ultra-high performance concrete provided by the present invention contains 10-15 parts, preferably 11-14 parts, more preferably 12-13 parts of a water-reducing agent. In the present invention, the water-reducing agent is preferably a polycarboxylic acid-based high-performance water-reducing agent. In the present invention, the fixed content of the polycarboxylic acid-based high-performance water-reducing agent is preferably 20%. In the present invention, the water-reducing ratio of the water-reducing agent is preferably ≧35%. In a specific embodiment of the present invention, the polycarboxylic acid-based high-performance water-reducing agent is preferably a polycarboxylic acid-based high-performance water-reducing agent produced by Jiangsu Subote Advanced Materials Co., Ltd.

[0033] Based on the mass fraction of the red mud, the rapid hardening ultra-high performance concrete provided by the present invention contains 80 to 100 parts of water, preferably 83 to 95 parts, and more preferably 85 to 93 parts.

[0034] Based on the mass fraction of the red mud, the high-speed hardening ultra-high performance concrete provided by the present invention contains 50-75 parts of steel fibers, preferably 55-70 parts, more preferably 60-65 parts. In the present invention, the length of the steel fibers is preferably 13 mm, the diameter is preferably 0.65 mm, and the tensile strength is preferably ≧2000 MPa. In the present invention, the steel fibers are preferably long and straight copper-plated steel fibers.

[0035] The present invention also provides a method for preparing the high-speed hardening ultra-high performance concrete described in the above technical solution, comprising: performing a first mixing process on the silica fume, cement, quartz sand and red mud to obtain a first premixture; performing a second mixing process on the first premix, water, and a water reducing agent to obtain a second premix; and performing a third mixing on the second premix and the steel fibers to obtain the high-speed hardening ultra-high performance concrete.

[0036] In the present invention, the first mixing is performed on silica fume, cement, quartz sand, and red mud to obtain a first premixture. In the present invention, the mixing time of the first mixing is preferably 120 to 180 s, more preferably 130 to 170 s. In the present invention, the equipment for the first mixing is preferably a mortar stirring pot. In the present invention, the first mixing is preferably stirring, the rotation speed of the stirring is preferably 135 to 145 rpm, more preferably 138 to 143 rpm, and the time is preferably 90 s.

[0037] After obtaining the first premix, the present invention performs a second mixing process on the first premix, water, and a water-reducing agent to obtain a second premix.

[0038] In the present invention, the mixing time of the second mixing is preferably 240 to 360 s, more preferably 250 to 350 s. In the present invention, the second mixing is preferably performed under stirring conditions, and the rotation speed of the stirring is preferably 135 to 145 rpm, more preferably 138 to 143 rpm.

[0039] After obtaining the second premix, the present invention performs a third mixing on the second premix and the steel fibers to obtain the high-early hardening, ultra-high performance concrete.

[0040] In the present invention, the mixing time of the third mixing is preferably 60 s. In the present invention, the third mixing is preferably carried out under stirring conditions, and the rotation speed of the stirring is preferably 135 to 145 rpm, more preferably 138 to 143 rpm.

[0041] The present invention also provides an application of the rapid hardening ultra-high performance concrete described in the above solution in building materials or decorative materials.

[0042] In the present invention, the application of the high-performance concrete of the high-strength, rapid-hardening type preferably includes the steps of pouring the high-performance concrete of the high-strength, rapid-hardening type into a mold, and then vibrating, standing and demolding the mold to obtain a prefabricated member; and maintaining the prefabricated member under steam maintenance conditions; Or, and sequentially performing injection and laminate maintenance on the high-speed hardening ultra-high performance concrete.

[0043] In the present invention, the vibration time is preferably 60 to 180 s, more preferably 70 to 170 s. In the present invention, the standing time is preferably 3 h, and the standing is preferably performed under a condition of covering with a plastic thin film. In the present invention, the steam maintenance conditions preferably include heating to 45°C at a rate of 5°C / min, performing preventive maintenance for 12 h, then heating to 100°C at a rate of 11°C / min, performing steam maintenance for 6 h, and finally cooling to room temperature at a rate of 6.7°C / h.

[0044] In order to further explain the present invention, the high-early hardening type ultra-high performance concrete provided by the present invention will be described in detail below with reference to the drawings and examples, but these should not be construed as limitations on the scope of protection of the present invention.

[0045] Example 1 Calculated by mass fraction, 72 parts of silica fume, 288 parts of cement, 119 parts of red mud, and 425 parts of quartz sand were mixed and added to a mortar mixing pot and stirred for 90 seconds at a rotation speed of 140±5 rpm to obtain a first premixture. 84 parts of water and 12 parts of water reducer were added to the obtained first premixture and stirred for 240 seconds at a rotation speed of 140±5 rpm. After the mortar was formed, 50 parts of steel fiber were added and stirred for 60 seconds at a rotation speed of 140±5 rpm to obtain an early-hardening, high-performance concrete.

[0046] The red mud in this fast hardening ultra high performance concrete replaced 40% of the original volume of cement and was recorded as VC40.

[0047] Example 2 Calculated by mass fraction, 72 parts of silica fume, 180 parts of cement, 148 parts of red mud, and 425 parts of quartz sand were mixed and added to a mortar mixing pot and stirred for 90 seconds at a rotation speed of 140±5 rpm to obtain a first premixture. 84 parts of water and 12 parts of water reducer were added to the first premixture obtained and stirred for 240 seconds at a rotation speed of 140±5 rpm. After the mortar was formed, 50 parts of steel fiber were added and stirred for 60 seconds at a rotation speed of 140±5 rpm to obtain an early-hardening, high-performance concrete.

[0048] The red mud in this fast hardening ultra high performance concrete replaced 50% of the original volume of cement and was recorded as VC50.

[0049] Example 3 Calculated by mass fraction, 72 parts of silica fume, 144 parts of cement, 178 parts of red mud, and 425 parts of quartz sand were mixed and added to a mortar mixing pot and stirred for 90 seconds at a rotation speed of 140±5 rpm to obtain a first premixture. 84 parts of water and 12 parts of water reducer were added to the first premixture obtained and stirred for 240 seconds at a rotation speed of 140±5 rpm. After the mortar was formed, 50 parts of steel fiber were added and stirred for 60 seconds at a rotation speed of 140±5 rpm to obtain an early-hardening, high-performance concrete.

[0050] The red mud in this fast hardening ultra high performance concrete replaced 60% of the original volume of cement and was recorded as VC60.

[0051] Comparative Example 1 Calculating by mass fraction, 72 parts of silica fume, 360 parts of cement, and 425 parts of quartz sand were mixed and added to a mortar mixing pot and stirred for 90 seconds at a rotation speed of 140±5 rpm to obtain a premix. 84 parts of water and 12 parts of water reducer were added to the premix and stirred for 240 seconds at a rotation speed of 140±5 rpm. After the mortar was formed, 50 parts of steel fiber were added and stirred for 60 seconds at a rotation speed of 140±5 rpm to obtain an ultra-high performance concrete without using red mud, which was recorded as Ref.1.

[0052] Comparative Example 2 Calculating by mass fraction, 69 parts of cement, 103 parts of red mud and 517 parts of quartz sand were mixed and added to a mortar mixing pan and stirred for 90 s under the condition of a rotation speed of 140 ± 5 rpm to obtain a premix, 86 parts of water were added to the obtained premix and stirred for 240 s under the condition of a rotation speed of 140 ± 5 rpm to obtain an ultra-high performance concrete without silica fume, water reducer and steel fiber, which was recorded as Ref. 2.

[0053] (Test example 1) The ultra-high performance concretes of Examples 1 to 3 and Comparative Examples 1 and 2 were subjected to tests for material set time, 3-hour strength, 28-day strength and durability, and the test methods were as follows.

[0054] Condensation time: Test the condensation time of UHPC mortar according to JGJ / T70-2009《Standard for basic performance test method of construction mortar》 Compressive strength and bending strength detection: The ultra-high performance concrete of the high-speed hardening type obtained in Examples 1-3 and the ultra-high performance concrete obtained in Comparative Examples 1-2 were respectively poured into a mold, and the mold was placed on a vibration table and vibrated for 180s to vibrate it tightly, and then a layer of plastic film was covered on the surface of the molded surface, and after 1d, the mold was demolded to obtain a prefabricated member, which was maintained under standard maintenance conditions (temperature 18-22°C, relative humidity greater than 95%), and after the maintenance was completed, the molded member was dried. The test was performed according to GB17671-1999 "Test method for strength of cement mortar", and the compressive strength and bending strength were tested using molded members of 40mm x 40mm x 40mm and 40mm x 40mm x 160mm, respectively, in a universal pressure tester. The durability was detected and tested using cylindrical molded components with a diameter of 100 mm and a height of 50±2 mm, and evaluated using an electric flux test and a quick chloride ion migration test (RCM).

[0055] The test results are shown in Table 1.

[0056] Table 1 Performance tests of ultra-high performance concretes of Examples 1 to 3 and Comparative Examples 1 to 2 JPEG2024545851000001.jpg38123

[0057] From Table 1, it can be seen that the initial condensation time of the ultra-high-performance concrete of the early-strength and fast-hardening type obtained by Examples 1 to 3 is short, the initial condensation can be achieved in 20 to 40 min, and the final condensation is completed within 60 min, the condensation time is short, and the 3h strength of the ultra-high-performance concrete of the early-strength and fast-hardening type obtained by Examples 1 to 3 is 15.1 to 22.7 MPa. The ultra-high-performance concrete of the early-strength and fast-hardening type obtained by Examples 1 to 3 has excellent 28d strength and durability, 28d strength > 100 MPa, reaches ultra-high strength, electric flux < 100C, belongs to the negligible range of chloride ion penetration. Comparative Example 1 is an ultra-high-performance concrete without red mud early-strength agent, its condensation time is 369 to 479 min, does not condense for 3 h, and does not meet the requirements of early-strength and fast-hardening concrete. Comparative Example 2 is a concrete system that contains only red mud early strength agent, and its early strength is low, only 1.1 MPa at 3h, and only 19.3 MPa at 28d. This shows that the amount of red mud needs to be significantly increased in order for the normal concrete system to achieve the rapid hardening effect, but the high amount of red mud significantly reduces the early strength of the normal concrete and also limits the subsequent strength evolution.

[0058] The electric fluxes of the ultra-high performance concretes of the high-speed hardening type obtained in Examples 1 to 3 of the present invention were all lower than those of the ultra-high performance concretes in Comparative Examples 1 and 2, which indicates that the durability performance of the ultra-high performance concretes of the high-speed hardening type provided by Examples 1 to 3 of the present invention is higher than that of the conventional ultra-high performance concrete of Comparative Example 1 and the ordinary concrete of Comparative Example 2.

[0059] (Test example 2) The ultra-high performance concrete of the high-speed hardening type obtained in Examples 1 to 3 was subjected to radioactivity and alkalinity tests. The test sample was ground to granules smaller than 0.16 mm, sealed and left for 7 days, and the radioactivity of each nuclide was tested using a low-power multi-channel gamma energy spectrometer to measure the internal irradiation index (I Ra ), external radiation index (I r ) was calculated and the statistical results are shown in Table 2.

[0060] Table 2: Radioactivity and alkalinity test results for Examples 1 to 3 JPEG2024545851000002.jpg43123

[0061] From Table 2, it can be seen that the ultra-high performance concrete of the high-early hardening type obtained in Examples 1 to 3 has a low specific radioactivity, 226 Ra specific radioactivity is 40-95Bq / kg, 232 The specific radioactivity of Th is 95-150Bq / kg. 40 The Ka specific radioactivity is 320-365Bq / kg and the internal and external irradiation index is I Ra and I r The values ​​of are all smaller than 1, and meet the internal and external irradiation indexes required by GB6566-2010 "Controlled Amounts of Radioactive Nuclides in Building Materials". + The product has low ion content and meets the safety standard for building materials GBT39804-2021 (Determination of leachable hazardous substances in wall materials).

[0062] According to the simplified life cycle assessment (Damineli BL, Kemeid FM, Aguiar PS, et al. Measuring the eco-efficiency of cement use[J]. Cement and Concrete Composites, 2010, 32(8):555-562) and Aitcin's research (Aitcin PC. Cements of yesterday and today: concrete of tomorrow[J]. Cement and Concrete Research, 2000, 30(9):1349-1359), the carbon emissions and costs under the unit performance index (1MPa) were used as indicators to evaluate the concrete environmental effects and benefits and economic benefits. The energy consumption (carbon dioxide emissions) and costs of the ultra-high-strength, early-hardening concrete obtained in Examples 1 and 2 and the ultra-high-performance concrete obtained in Comparative Example 1 were compared, and the results are shown in Table 3.

[0063] Table 3. Energy consumption and cost comparison table for concrete JPEG2024545851000003.jpg81121

[0064] From Table 3, it can be seen that the energy consumption and cost of preparing ultra-high performance concrete is high, and the carbon dioxide emissions are 462.9 kg / m 3 The cost is 4274 yuan / m 3 It was found that the ultra-high performance concrete of the high-early hardening type provided by the present invention has low energy consumption and low cost, and the carbon dioxide emission of VC60 is 138.5 kg / m 3 The cost of VC60 is 2309 yuan / m 3 It can be seen that the preparation cost and energy consumption of the high-early hardening ultra-high performance concrete provided by the present invention are both lower than those of ordinary ultra-high performance concrete.

[0065] Take VC60 as an example, it can reduce the preparation cost per cubic meter of ultra-high performance concrete, reduce CO2 emissions by 70.7%, and solidify and recover 371 kg of red mud. Take an actual bridge construction as an example, laying a 15 cm thick steel-ultra-high performance concrete composite bridge deck, of which the total amount of ultra-high performance concrete used is 6618.8 m 3 Statistics on the amount of concrete used in bridge decks are shown in Table 4.

[0066] Table 4. Statistical table of ultra-high performance concrete used for bridge decks JPEG2024545851000004.jpg6898

[0067] From Table 4, it can be seen that by selecting the ultra-high performance concrete prepared by the present invention, the direct cost can be reduced by about 12.98 million yuan, the carbon dioxide emission treatment cost can be reduced by 470,000 yuan (the treatment cost is calculated according to 0.22 yuan / kg), and the red mud can be solidified by about 1,200 tons.

[0068] From the above examples, it can be seen that the high-early-strength, high-hardening ultra-high performance concrete provided by the present invention not only has higher early strength and shorter solidification time, but also has super-high later strength, which meets the strength and construction time requirements of bridge structure construction and ultra-high performance concrete laying decorative members, while having relatively high durability performance, low preparation cost, low energy consumption, and also achieving safe and efficient recycling and reuse of red mud.

[0069] The above description of the examples only contributes to understanding the method of the present invention and its core idea. It should be noted that those skilled in the art can make some improvements and modifications to the present invention without departing from the principles of the present invention, and these improvements and modifications are also included in the scope of protection of the claims of the present invention. Those skilled in the art will recognize that several modifications to these examples are obvious, and the general principles defined in this specification can be realized in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention is not limited to these examples shown in this specification, but belongs to the widest scope consistent with the principles and novel features disclosed in this specification.

Claims

1. It is a high-performance concrete with rapid hardening and strengthening properties, and when calculated by mass fraction, A rapid hardening, ultra-high performance concrete containing the following ingredients: 110-180 parts of red mud, 70-80 parts of silica fume, 130-290 parts of cement, 400-500 parts of quartz sand, 10-15 parts of water reducer, 80-100 parts of water, and 50-75 parts of steel fiber.

2. The particle size of the quartz sand is 0.075 to 0.6 mm; The particle size of the red mud is 0.01 to 0.075 mm; 2. The ultra-high performance concrete of claim 1, wherein the silica fume has an average particle size of 300 nm and an activity index of 100% or more.

3. The ultra-high performance concrete of claim 1, characterized in that the water reducing agent is a polycarboxylic acid-based high performance water reducing agent, the fixed content of the polycarboxylic acid-based high performance water reducing agent is 20%, and the water reduction rate is ≧35%.

4. 2. The ultra-high performance concrete of claim 1, wherein the cement is ordinary Portland cement having a strength level of 52.

5.

5. 2. The ultra-high performance concrete of claim 1, wherein the steel fibers have a length of 13 mm, a diameter of 0.65 mm, and a tensile strength of ≧2000 MPa, and the steel fibers are long and straight copper-plated steel fibers.

6. 3. The ultra-high performance concrete of claim 1, wherein the red mud is a Bayer process red mud.

7. The specific gravity of the quartz sand is 2560 kg / m 3 3. The ultra-high performance concrete of claim 1 or 2, characterized in that:

8. performing a first mixing process on the silica fume, cement, quartz sand and red mud to obtain a first premixture; performing a second mixing process on the first premix, water, and a water reducing agent to obtain a second premix; and performing a third mixing for the second premix and the steel fibers to obtain the high-speed hardening ultra-high performance concrete.

9. The method according to claim 8, wherein the mixing time of the first mixing is 120-180s, the mixing time of the second mixing is 240-360s, and the mixing time of the third mixing is 60s.

10. Application of the rapid hardening ultra-high performance concrete according to any one of claims 1 to 7 or the rapid hardening ultra-high performance concrete obtained by the preparation method according to any one of claims 8 to 9 in building materials or decorative materials.

11. The application is A step of injecting a high-speed hardening ultra-high performance concrete into a mold, and then vibrating, leaving and demolding the mold to obtain a prefabricated member; maintaining the prefabricated element under steam maintenance conditions; or Or, 11. The application of claim 10, further comprising a step of sequentially pouring and laminating maintenance for ultra-high performance concrete of the rapid hardening type.

12. The application according to claim 11, characterized in that the duration of said vibration is between 60 and 180 s.

13. 12. The application according to claim 11, characterized in that the standing time is 3 h.

14. The application of claim 11, wherein the steam maintenance conditions include: increasing the temperature to 45°C at a rate of 5°C / min, performing preventive maintenance for 12 hours, then increasing the temperature to 100°C at a rate of 11°C / min, performing steam maintenance for 6 hours, and finally cooling to room temperature at a rate of 6.7°C / h.

Citation Information

Patent Citations

  • Ecological ultra-high performance concrete

    CN109836097A

  • Concrete structure and production thereof

    JP1989261253A

  • Hydraulic composition

    JP2002338323A

  • Building material containing treated bauxite waste and method for producing the same

    JP2004530544A

  • Porous particulate material for fluid treatment, cementitious composition and method of making same

    JP2007516922A